Trademark Registration in Bad Faith in the People’s Republic of China – Causes and Analysis of Provisions of Chinese law - Ratajczak, Oskar (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
Bad faith trademark registrations in the People’s Republic of China are a longstanding issue. The PRC’s Trademark Law amendment of 2019 changed some articles relating to the bad faith trademark registration. The goal of this Article is to analyse the sources of this issue and examine the provisions of Chinese Trademark Law to understand how well foreign entities are protected against trademark squatters after the 2019 amendment. The causes of this issue were found in China’s unique economic position, the Chinese language, Chinese society, and Chinese culture. The analysis of the amended version of PRC’s Trademark Law found that, in fact, the Chinese legislator made some enhancements, but unfortunately it seems it is not going to be sufficient to protect the rightful foreign owners of trademarks in an effective way.